Modelo de comunicação verbal com o cego : desenvolvimento e validação em consulta de enfermagem - Costa, Katia Neyla de Freitas Macêdo (2009)
Although blind people have limitations, this cannot impede their communication and relationship with other people. In academic education, however, health professionals, such as nurses, are not prepared to take care of blind people. This study aimed to validate a Verbal Communication Model with the Blind and the nurse in the light of Roman Jakobson’s Theory. A quantitative study was a methodological approach was carried out at the LabCom_Saúde of the Nursing Department at the Federal University of Ceará, Brazil, between December 2007 and December 2008, using filming. The environment was organized for the sake of maximum similarity with a nursing consultation room for the screening of blind diabetes patients. Participants were 30 newly-graduated nurses and graduates of the Nursing course and 30 patients blind in both eyes and their possible companions. The specialists who assessed the model and the judges who analyzed the filming collaborated in the research, in view of their degree, scientific production and work on the theme. After the construction, the model was assessed by three specialists for face and content validation. After the assessment, modifications were incorporated. To test the model, 30 nursing consultations were registered and filmed. Fifteen of these were under the responsibility of untrained and 15 under the responsibility of trained nurses. The films were analyzed by three judges, who were nurses with training on the Communication Model. All principles of Resolution 196/96 were complied with. Data were processed in Statistical Package for Social Sciences (SPSS) software and analyzed through univariate tables with relative frequency and percentage. Seventeen (56.7%) of the nurses were between 22 and 25 years of age, and a majority, 26 (86.7%), were women. Eight (26.7%) blind patients were between 39 and 49 years old and most of them, 16 (53.4%), were women; 20 (66.7%) became blind when they were between 21 and 35 years of age. The model was constructed in four phases: general guidelines; welcoming; data collection; nursing interventions. In the general guidelines, the trained group obtained excellent results on all times, ranging from 60% to 91.1%. The non-trained group showed very bad/bad communication, with higher frequencies on four items, using words that indicate direction (97.8%); lightly touching the arm or shoulder (95.6%); avoiding gestures (68.9%); talk while looking at the blind (22.2%). In the welcoming phase, all trained nurses displayed a successful performance, as opposed to the non-trained nurses: 100% very bad or bad in some actions. In the data collection phase, the trained group obtained an excellent performance on five of the actions and, in the nursing diagnosis and planning phases, trained nurses presented good and excellent actions for the following items: following the protocol (95.6%); informing on the reason for the silence when making notes (93.4%); and avoiding long periods of silence (100%). The performance of the non-trained group was considered very bad in terms of notes because they did not inform on the reason for the silence (100%); avoiding long periods of silence (91%). In the nursing intervention phase, the trained group achieved excellent performance on all items, without any very bad/bad actions on any of the items in the assessment phase. In the final phase of the consultation, excellent performance of the trained nurses was identified on the following items: communicates while accompanying the blind to the door (82.2%); says goodbye while talking and shaking hands (62.2%); and strengthens the information (42.2%). In the analysis of verbal communication between the nurse and the blind, the vocative function presented 65.7% of actions, against 19.5% for the imperative function. Silence was manifested in almost half (45%) of interactions with non-trained nurses against 12.4% for trained nurses. In the trained group, empathy (69.2%), tranquility (49.6%), satisfaction (44.2%) and solidarity (29.4%) were also present. The most evidenced channel in the trained group was speech (86.8%). And common language occurred in the trained group’s (85.6%) and the non-trained group’s (50.1%) interactions. In conclusion, the model was validated by the sample and it can be affirmed that the Verbal Communication Model is effective. Thus, its use in nursing consultations with blind people is recommended.